The Relationship among Climate Change Vulnerability, Fossil Fuel Energy, Economic Development, Financial Development, Institutional Quality and Population Growth in 36 Developed Countries - Makhmudov, Samariddin; Mirzaev , Fayzulla; Jiyanova, Nargiza; Rejapov, Saydulla; Matyakubova, Gulnoza; Saidov, Otabek; Allaberganov, Sherali (International Journal of Energy Economics and Policy, 2025)
The research assesses the impact of fossil fuel energy consumption on climate change vulnerability for 36 developed nations using the time period of 2000-2022. For the empirical results, Canay (2011) fixed effects quantile regression is employed. The outcome indicates that fossil fuel energy positively and significantly impacts on climate change vulnerability across all the quantiles. These findings validate the theoretical linkage and economic intuition as well. Policy implications should consider the role of fossil fuel energy in shaping climate change policy. Furthermore, the factors such as economic development, financial development, institutional quality and population growth should be considered in the relationship between fossil fuel energy and climate change vulnerability.